The Effect of Adding Steel Fibers and Graphite on Mechanical and Electrical Behaviors of Asphalt Concrete - M. Messaoud; B. Glaoui; O. Abdelkhalek (Salehan Institute of Higher Education, 2022)
Conductive asphalt concrete can satisfy different and multifunctional applications such as heating roads to get rid of snow and ice and assure auto-detection, auto-cure, and energy recovery. This research aims to evaluate the performance of asphalt concrete with additives like steel fibers and graphite powder. This work is based on destructive tests (direct tensile test FENIX) and non-destructive tests (electrical resistivity measures). The obtained results indicate that the tensile resistance, dissipated energy, and ductility module of asphalt concrete increased with the increasing steel fiber percentage. Direct tensile strength, cracking resistance, and dissipated energy increased as graphite percentage increased, while the ductility module decreased. Electrical resistivity decreased when it added steel fibers and graphite. Therefore, it found that tensile strength increased reversibly with electrical resistance. When adding steel fibers or graphite powder, the dissipated energy of asphalt concrete is increased while electrical resistivity is decreased. The dissipated energy of conductive asphalt concrete with steel fibers is higher than that with graphite powder. Electrical resistivity decreased significantly with increasing steel fibers, compared to electrical resistivity with graphite. The obtained results indicate that asphalt concrete cracking resistance is higher with the optimal percentage of steel fibers added at 1% and better mechanical performance. Doi: 10.28991/CEJ-2022-08-02-012 Full Text: PDF